Struktur Klausa dalam Berita Online Detik.com terkait Mahasiswa UNNES Iko Juliant Junior Periode September 2025 - Fitri Eka Lestari; Rahmah Maulida Dwi Aryani; Salsabila Dwi Apriani; Jenicka Shakilla Hernanda; Irenata Sitanggang; Asep Purwo Yudi Utomo; Septina Sulistyaningrum; Zuyyinatul Mushoffa (Pusat Riset dan Inovasi Nasional, 2026)
This study discusses clause structures in online news articles published by Detik.com, highlighting the issue of UNNES student Iko Juliant Junior in September 2025. The background of this research lies in the importance of understanding how digital media utilize language structures to convey information effectively, concisely, and objectively. In the context of online journalism, the selection and arrangement of clauses play a crucial role in shaping clarity, focus, and meaning as perceived by readers. The purpose of this study is to describe the forms and types of clauses used in news texts and to explain their functions in maintaining the accuracy and credibility of information delivery. The research employs a qualitative descriptive method with a focus on syntactic studies. The data consist of clauses found in Detik.com news articles published in September 2025, analyzed based on their syntactic components: subject, predicate, object, complement, and adverbial. The findings show that the clause patterns of Subject–Predicate (S–P) and Subject–Predicate–Object (S–P–O) are the most dominant, with verbal predicates appearing most frequently. These patterns reflect the efficient, factual, and easily understood style of online journalistic language. This study contributes to the development of syntactic research and serves as a practical reference for journalists and readers in understanding effective language use in digital media.